Ethics, law, and politics in palaeontological research: The case of Myanmar amber - Dunne, Emma; Raja, Nussaïbah Begum; Stewens, Paul P.; Zin-Maung-Maung-Thein; Zaw, Khin (Communications Biology, 2022)
Fossil material in amber from Myanmar can provide important insights into mid-Cretaceous forest ecosystems. However, Myanmar amber has been receiving increased international attention due to reported links between amber mining and the ongoing humanitarian crisis in northern Myanmar, as well as the legal issues associated with its exportation. Here, we conduct a bibliometric analysis of Myanmar amber publications (1990–2021) and demonstrate how research interest in Myanmar amber is explicitly linked to major political, legal, and economic changes. An analysis of the authorship networks for publications on amber inclusions reveals how current research practices have excluded Myanmar researchers from the field. In addition, the international trade of Myanmar amber with fossil inclusions falls into a legal ‘grey-zone’ which continues to be exploited. This case study vividly demonstrates that systemic changes, alongside an increased awareness of inequitable research practices amongst the broader scientific and allied communities, are urgently needed to curb illegal practices in palaeontology.
CRIS-Team Scopus Importer:2022-10-14